Heterogeneity of tumor endothelial cells. Issue 11 (12th September 2013) - Hida, Kyoko; Ohga, Noritaka; Akiyama, Kosuke; Maishi, Nako; Hida, Yasuhiro
Abstract : Tumor blood vessels play important roles in tumor progression and metastasis. Thus, targeting tumor blood vessels is an important strategy for cancer therapy. Tumor endothelial cells (TECs) are the main targets of anti‐angiogenic therapy. Although tumor blood vessels generally sprout from pre‐existing vessels and have been thought to be genetically normal, they display a markedly abnormal phenotype, including morphological changes. The degree of angiogenesis is determined by the balance between the positive and negative regulating molecules that are released by tumor and host cells in the microenvironment. Reportedly, tumor blood vessels are heterogeneous with TECs differing from normal endothelial cells (in contrast to the conventional view). We recently compared characteristics of different TECs isolated from highly and low metastatic tumors. We found TECs from highly metastatic tumors had more proangiogenic phenotypes than those from low metastatic tumors. Elucidating the variety of TEC phenotypes and identifying TEC molecular signatures should lead to more complete understanding of the mechanisms of tumor progression, discovery of new therapeutic targets, and development of biomarkers. This review considers current studies on TEC heterogeneity and discusses the therapeutic implications of these findings.